GROWTH OF GREEN SAWY (BRASSICA JUNCEA L.) AFTER FERTILIZED LIQUID ORGANIC FERTILIZER - Sukarman Hadi Jaya Putra (Pro-STek, 2023)
This study aims to determine the effect of applying liquid organic fertilizer on the growth and production of mustard greens (Brassica juncea L.) with a hydroponic system. This study used a completely randomized design (CRD) consisting of 4 treatments and 3 replications, namely 15 ml/985 ml water (P1), 20 ml/980 ml water (P2) and 25 ml/975 ml water (P3). as well as the control treatment, namely 0 ml/1000 ml of water (P0). The data collection method was carried out quantitatively by measuring the growth of mustard greens (Brassica juncea L.) which included plant height, number of leaves, leaf width and fresh weight of mustard greens (Brassica juncea L.). The data obtained in the normality and homogeneity tests, if the data results are normal and homogeneous, then they are analyzed with the One Way-Anova test, if the data is significant then proceed with the Tukey test. The results of the study showed that the application of fermented liquid organic fertilizer from cow dung at different doses had a significant effect on the number of leaves but had no significant effect on the height of mustard greens (Brassica juncea L.). The effect of applying fertilizer with a concentration of 25 ml/975 ml of water was greater with plant height (21.73 cm) and number of leaves (12A strands).